A novel technique for developing a dual-phase steel with a lower strength difference between ferrite and martensite. (June 2020) - Chen, Chih-Yuan; Li, Cheng-Han; Tsao, Tzu-Ching; Chiu, Po-Han; Tsai, Shao-Pu; Yang, Jer-Ren; Chiang, Lung-Jen; Wang, Shing-Hoa
Abstract: It is generally accepted that reducing the strength difference between soft ferrite and hard martensite in a dual-phase (DP) steel can delay fracture during plastic deformation. However, it is still not clear whether the better approach to attain the goal is to decrease the strength of martensite or to increase the ferrite strength. In the present paper, low carbon steel was microalloyed with Ti and Cu to alleviate the strength difference between the hard martensite and soft ferrite phases. The results showed that the Vickers hardness (HV0.1 ) differences between ferrite and martensite after tempering at 500 °C for 8 h were ∼9 HV0.1 for Ti-Cu DP steel and ∼83 HV0.1 for Ti DP steel. It is found that Cu particles that precipitate on the pre-existing titanium carbide can increase the strength of ferrite and martensite after long time aging.